2017
DOI: 10.1002/2017gl072630
|View full text |Cite
|
Sign up to set email alerts
|

Emergent archetype patterns of coupled hydrologic and biogeochemical responses in catchments

Abstract: Relationships between in‐stream dissolved solute concentrations (C) and discharge (Q) are useful indicators of catchment‐scale processes. We combine a synthesis of observational records with a parsimonious stochastic modeling approach to test how C‐Q relationships arise from spatial heterogeneity in catchment solute sources coupled with different timescales of reactions. Our model indicates that the dominant driver of emergent archetypical dilution, enrichment, and constant C‐Q patterns was structured heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
209
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(225 citation statements)
references
References 56 publications
16
209
0
Order By: Relevance
“…Previous interpretations of event‐scale C‐Q hysteresis have focused on the mixing of hydrologic sources (Bowes et al, ; Chanat et al, ; Evans & Davies, ; Hoeg, Uhlenbrook, & Leibundgut, ), biogeochemical transformations (Bowes et al, ; Butturini et al, ), and variability of end‐member concentrations (Chanat et al, ) as drivers of observed patterns. Similarly, investigations of longer term C‐Q dynamics incorporating data from multiple storm events over many years have focused on comparing the broad‐scale behaviour of solutes across flow regimes within a single catchment and across multiple catchments (Godsey et al, ; Herndon et al, ; Musolff et al, ; Musolff, Fleckenstein, Rao, & Jawitz, ; Thompson et al, ). Our results are consistent with the general interpretations of biogeochemical source and hydrologic flowpath dynamics presented in these previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous interpretations of event‐scale C‐Q hysteresis have focused on the mixing of hydrologic sources (Bowes et al, ; Chanat et al, ; Evans & Davies, ; Hoeg, Uhlenbrook, & Leibundgut, ), biogeochemical transformations (Bowes et al, ; Butturini et al, ), and variability of end‐member concentrations (Chanat et al, ) as drivers of observed patterns. Similarly, investigations of longer term C‐Q dynamics incorporating data from multiple storm events over many years have focused on comparing the broad‐scale behaviour of solutes across flow regimes within a single catchment and across multiple catchments (Godsey et al, ; Herndon et al, ; Musolff et al, ; Musolff, Fleckenstein, Rao, & Jawitz, ; Thompson et al, ). Our results are consistent with the general interpretations of biogeochemical source and hydrologic flowpath dynamics presented in these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pools of exogenous solutes such as NO 3 − and SO 4 2− are likely less spatially extensive than the source pools of geogenic solutes, legacy stores of these constituents can accumulate in soils under conditions of chronic, elevated atmospheric deposition, or the application of agricultural fertilizers. Accumulation of such legacy stores has been invoked as a potential explanation for the biogeochemical stationarity observed in a variety of managed systems (Basu et al, ; Dupas, Jomaa, Musolff, Borchardt, & Rode, ; Musolff et al, ; Musolff et al, ). White Clay Creek is located in the mid‐Atlantic USA; this region was subjected to some of the highest rates of chronic atmospheric NO 3 − and SO 4 2− deposition in North America between the 1970s and early 2000s (Driscoll et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…although many studies have characterized C–Q relationships across watershed sizes, few have explicitly explored controls on these relationships (but see Musolff et al, ). Our hypothesis that dominant controls included watershed size, land cover, and lithology was not well supported, supporting results from Godsey et al ().…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of export regimes in contrasting catchments representing different landscape types can be performed to investigate the effect of, for example, contrasting dominant land use, dominant flow paths or climate (Outram et al, 2014;Dupas et al, 2017;Minaudo et al, 2017), sometimes aided by the use of models (e.g., Dupas et al, 2016a;Hartmann et al, 2016). In headwater catchments, several studies have highlighted the important role of landscape heterogeneity within hillslopes (Herndon et al, 2015;Musolff et al, 2017), notably the crucial role of reactive zones such as riparian wetlands (Dick et al, 2015;Pinay et al, 2015;Tiwari et al, 2017) in controlling solute export regimes.…”
Section: Introductionmentioning
confidence: 99%